Internet connectivity disruption in UAE (United Arab Emirates) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in United Arab Emirates. Data sourced from IODA.
Network Disruption Incident ID: AE-2026-0284. Severity: critical. Confidence: 70%